Clozapine-Induced Myocarditis: Is Mandatory Monitoring Warranted for Its Early Recognition?. (23rd January 2014) - Munshi, T. A.; Volochniouk, D.; Hassan, T.; Mazhar, N.
Abstract : Clozapine is an atypical antipsychotic used for treatment resistant schizophrenia. Its potential to induce agranulocytosis is well known but it can also cause myocarditis. Clozapine is the only antipsychotic known to induce this side effect, typically early in the treatment, and literature is scarce on this condition. We are presenting a case report of a 21-year-old schizophrenic male who developed myocarditis within 3 weeks of starting on clozapine for his treatment resistant psychosis. We then aim to review some of the available literature and raise awareness among physicians as this condition can potentially be fatal if not detected early.